Motion Control Modeling and Simulation of the Thruster Mechanism of a Boring Machine - Wang Shuanghua; Wang Jianwei (Jixie chuandong)
The thruster mechanism of which two neighboring thruster cylinders are wedge-shape arranged is a redundant driving multi-DOF parallel mechanism.It is very complex to control its motion due to the complexity of the mechanism and the coupling between the driving rods,so a method of establishing inverse kinematics model of the thruster mechanism and graphical model with the SimMechanics in the environment of Simulink diagram design in MATLAB is presented and then connect them by controller.The trajectory tracking control of parallel mechanism is realized and this method is intuition and convenience.A foundation for the precious control of thruster mechanism is laid and it is provide convenience for establishing simulation models of other multi-body dynamic system.